Metodología para el diseño y dimensionamiento de sistemas domóticos para viviendas - Pucha Quizhpe, Armando Patricio (2023)
In this research work, a methodology for a home automation system adaptable to all types of housing is presented that provides and guarantees greater control and intelligent management of energy savings, security, comfort and communication with the entire home automation system of the home. In relation to the communications aspect, teleoperation can be carried out, that is, all the devices of the home automation system can be controlled and supervised wirelessly by all the users or members of the home. These communications will be bidirectional since the user will be able to establish communication with the home automation systems in the home, through smart devices. The home automation system that has been designed and implemented in a test bench uses actuators to carry out lighting and blinds control actions. In addition, there is a control interface accessible only by the user via the Internet, the HDL Bus Pro application development tool is used, which works with the KNX communication language, which is one of the most versatile communication protocols, useful and with the largest variety of home automation equipment on the market. Keywords: Keywords: home automation system, KNX communication language, HDL Bus Pro applications.